Optimising health economic evaluations for geriatric cancer patients - Goettler, Andrea; Kessel, Tanja-Maria; Sonntag, Diana (Gesundheitsökonomie & Qualitätsmanagement, 2018)
Aim Despite the growing number of elderly cancer patients, health economic evaluations have not put enough attention on this patient group. We reflect on the current state of health economic evaluations for geriatric patients and present suggestions for improvements.Method We reviewed the scientific literature on health economic evaluations for geriatric patients in Germany and internationally. Additionally, we conducted a scoping review on cost-utility analyses on cancer treatment for older patients (> 60 years).Results The literature review resulted in eight relevant studies. Besides the paucity of economic evaluations for elderly patients, we also present quality limitations. From the literature, we identify four recommendations regarding cost calculation, geriatric assessment, patient decision-making and quality of life on how to design better economic evaluations for geriatric cancer treatment.Conclusion The demographic change requires more attention regarding elderly patients in health economics. Including patients above 70 years of age in health economic evaluations and improving cost-utility analyses will help to improve resource allocations and effective healthcare for the elderly.
Keywords: health economics; oncology; geriatrics; cost-utility analysis; geriatric assessment